Four-parameter electromagnetic method for determining the parameters of brewery effluents - Sebko, V. V.; Pyrozhenko, Ye. V.; Zashchepkina, N. M.; Zdorenko, V. G.; Markina, O. M. (World academy of materials and manufacturing engineering, 2022)
Purpose: of the article is to study a four-parameter electromagnetic method for joint measurements of electrical resistivity k, relative permittivity εr, temperature t and density ρ of samples of acidic, alkaline and average effluents from a microbrewery based on a magnetic flux probe (MFP), which considers the influence of informative parameters of beer effluents on the components of the amplitude and phase signals of a multiparameter device. Design/methodology/approach: The implementation of the four-parameter method is carried out on the basis of the dependences G1 = f (A1) and G2 = f (A2) at two frequencies of the electromagnetic field f0 and f1 for acid, alkaline and average effluent and allows you to jointly determine the four parameters of effluent samples with the same converter in the same control area. The proposed method makes it possible to improve the accuracy of identifying effluent samples since the obtained multiparameter information makes it possible to determine the nature and properties of effluent samples using only one transducer with certain physical characteristics. The research results lead to the expansion of the technical capabilities of electromagnetic measurement methods, as well as to an increase in the metrological characteristics of electromagnetic transducers and an increase in the accuracy of measuring the parameters of effluent samples compared to reference methods and measuring instruments. Thus, the implementation of this approach contributes to the prediction and prevention of the reasons for the deviation of beer effluent samples from the specified indicators of environmental safety. Findings: The universal conversion functions MFP have been established, connecting the amplitude and phase components of the converter signals with the parameters k, εr, t and ρ of acidic, alkaline and average effluents. Based on the universal transformation functions G1 = f (A1) and G2 = f (A2), a four-parameter electromagnetic method for joint measurements of electrical resistivity k, relative permittivity εr, temperature t and density ρ of acidic, alkaline, and average effluents from breweries has been developed. When conducting research at two close frequencies of the electromagnetic field f0 = 20.3 MHz and f1 = 22 MHz, algorithms were obtained for measuring and calculating procedures for determining k, εr, t and ρ for samples of acidic, alkaline and average effluents from the brewing industry. Research limitations/implications: Research perspectives consist in the creation of automated systems for multiparameter measuring control of the physicochemical characteristics of acidic and alkaline effluent from food and processing industries based on the immersed electromagnetic transducer. Based on the data obtained using informative methods to measure the parameters of effluent samples, an integrated method for treating beer effluents of various compositions will be proposed. At the same time, the scheme of the integrated treatment method should include a filter that provides the introduction of a magnetic fluid and a separation device that allows us to remove a fraction, including pollution in itself. Practical implications: Is that the proposed four-parameter electromagnetic method makes it possible to determine to what composition the controlled samples of wastewater should be attributed (acidic or alkaline). It, in turn, makes it possible to choose a rational method for treating beer effluents and to prevent the reasons for the deviation of effluent samples from the environmental safety indicators set by the standards. Originality/value: of the article is the research related to the expansion of the functional and technical capabilities of the electromagnetic two-frequency transducer MFP through the implementation of a four-parameter electromagnetic method of joint measurements of electrical resistivity k, relative permittivity εr, temperature t and density ρ of acidic, alkaline and average effluents from breweries. The universal transformation functions G1 = f (A1) and G2 = f (A2) found in the work at two close magnetic field frequencies, f0 = 20.3 MHz and f1 = 22 MHz, make it possible to control four physicochemical parameters of acidic, alkaline and average wastewater at the same time by the same MFP. An algorithm has been developed for determining the signal components of a two-frequency thermal MFP, the ranges of which correspond to the ranges of changes in electrical resistivity k, relative permittivity εr, temperature t and density ρ of acidic, alkaline, and average brewery effluents. The basic relations that describe the two-frequency four-parameter electromagnetic method of joint measurements of the physicochemical parameters of acidic, alkaline and averaged beer effluents have been obtained.
Keywords: four-parameter electromagnetic method; brewery effluents; magnetic flux probe (MFP); conversion functions; joint measurements; electrical conductivity; relative permittivity; density; temperature